Badminton as one of the means of health and recreational activities of students - Olga Sutula; Anastasia Nevelyka; Yuri Chucha (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to assess the influence of badminton classes according to the health-improving and recreational program on the physical fitness and health of students. Material and methods: 13 female applicants for higher education of the second year of the Kharkov State Academy of Physical Culture took part in the study. The health-improving and recreational program was implemented within 6 months. To assess its effectiveness at the beginning and at the end of the experiment, the participants were determined by anthropometric indicators (body weight, standing height, muscle strength of the hand), physiological indicators (vital capacity of the lungs (VC)). The assessment of the physical working capacity of female students and the effectiveness of their respiratory system was carried out using the tests of Rufier, Shtange, Genche. The level of their health was assessed according to Pirogova's method. Results: the studies carried out confirmed the information of scientists about the unsatisfactory state of physical fitness and the level of health of student youth. The presented materials made it possible to state the positive influence of health-improving and recreational classes using badminton means on the indicators of the functional state of the cardiovascular and respiratory systems, the level of physical performance and physical health of girls. Conclusions: the results of the studies indicate that the indicators of body weight, standing height did not change almost, and indicators of hand strength, vital capacity of the lungs improved during the cycle of training sessions. The results of the conducted research testify to the improvement of the functional state and the level of health of the female students, who trained according to the health-improving and recreational program, which is based on the means of badminton.